DEVELOPMENT OF E-MODULE MEDIA USING THE CANVA APPLICATION IN LEARNING READING COMPREHENSION SKILLS OF GRADE IV STUDENTS OF SD NEGERI KARING-KARING BAUBAU CITY - Fatmala, Kiki; Syatriana, Eny; A. Arif, Tarman (Jurnal Konseling Pendidikan Islam, 2025)
This study is a development research aimed at describing the prototype, validity, practicality, and effectiveness of an e-module using the Canva application in teaching reading comprehension skills to fourth-grade students at SD Negeri Karing-Karing, Baubau City. The development model used is the Four-D (Define, Design, Develop, and Disseminate). Data were collected through expert validation instruments, media and material expert assessments, teacher and student practicality questionnaires, observation sheets, and reading comprehension tests. The results showed that (1) the developed media was an interactive e-module; (2) the validity level was categorized as very feasible with an average score of 98.12% from media experts and 97.31% from content experts; (3) practicality was rated very practical based on observation sheets (97.5%) and teacher questionnaires (95.45%); (4) the media was effective in improving reading comprehension skills, as indicated by student responses (93.61%) and a significant increase from pretest (45.23%) to posttest scores (95.23%). This study concludes that the Canva-based e-module is valid, practical, and effective in enhancing students’ reading comprehension skills. These findings indicate that the e-module can serve as an innovative and applicable learning alternative.